The Relation between BURT Radio Telescope Antenna Movement in Horizontal Coordinates Relative to Equatorial Coordinates - Latif, Sama Abd-alrazaq; Abood, Kamal M. (Iraqi Journal of Science, 2025)
The antenna of the Baghdad University Radio Telescope (BURT), located at Baghdad longitude (44.38°) and latitude (33.275°), is moved according to a horizontal coordinate (Azimuth (Az), Elevation (El)) system. In this paper, the relation between antenna telescope movement is converted to equatorial coordinates (Right Ascension (RA), Declination (DEC)) using a set of conversion equations. MATLAB R2014a is used for programming all equations. Sun data observations for the BURT radio telescope archive are used to investigate the relationship between horizontal and equatorial coordinates. Two sets of data are selected to test and verify this relationship. The first set of data is for sun observation on 7 January 2019 at 10:50 AM, and the second on 13 April 2019 at 11:18 AM. The SunCalc software package (https://www.suncalc.org/ ) is used to calculate the sun’s location (Az, El) in Baghdad’s sky. The antenna movement in horizontal coordinates (Az, El) to form a square area equal to 4° square will be converted to equatorial coordinates in the sky region boundary of -24.9313°≤DEC≤ -19.8238° and 19h 17m 2s ≤RA≤19h 37m 20s. In the same way, the antenna movement in horizontal coordinates (Az, El) to form a square area equal to 3° square will be converted to equatorial coordinates in the sky region boundary of 7.3242°≤DEC≤10.6877° and 1h 29m 47s ≤RA≤1h 39m 56s